SIRI’ DALAM PERSPEKTIF DAKWAH ISLAM - Murniaty Sirajuddin (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Siri 'as the cultural aspects of the Bugis community contains the value of the propagation of Islam .. this paper aims to reveal the meaning of siri' and its value in Makassar Bugis community in relation to the propagation of Islam. Siri is a system of social values and personality cultural institutions of self defense and human dignity as individuals and members of society must be maintained and preserved both in public life and in the life individi. Siri is an abstract thing that can be seen only manifestations sometimes positive and sometimes negative. Siri 'encourage someone to do good and controllers for not doing bad, between Siri and the propagation of Islam has a close relationship especially after Islam was accepted as part of panngaderreng